Differential distribution of protein kinases along the crypt-to-lumen regions of rat colonic epithelium. Issue 9 (September 1988) - Schwartz, B; Fraser, G M; Levy, J; Sharoni, Y; Guberman, R; Krawiec, J; Lamprecht, S A
Abstract : The activity of cAMP-dependent and cAMP-independent protein kinases, a class of enzymes involved in the regulation of cell proliferation was measured in rat colonic epithelium. Sequential cell populations harvested by a stepwise scraping technique from colonic crypt regions were identified by histology and incorporation of [3H]-thymidine into DNA. cAMP-independent phosphorylation of casein, in the presence of [gamma-32P]ATP, was markedly suppressed by quercetin, a bioflavonoid known to inhibit G-type casein kinase, protein kinase-C and tyrosine protein kinase. Conversely, the cyclic nucleotide regulatable form requiring histone as substrate was responsive to the action of the heat stable protein kinase inhibitor. The protein kinase species were characterised and partially purified by DEAE-cellulose chromatography. The activity of cAMP-dependent protein kinase in colonic cytosols (pmol 32P/min/mg protein, means (SE)) increased from 129.4 (15.9) in superficial cell populations to 238.5 (31.4) in lower crypt cell fractions (p less than 0.01). Colonic cAMP-independent protein kinase activity increased from 87.3 (15.6) in surface cell preparations to 178.1 (30.0) in lower crypt cell populations (p less than 0.02). A comparable activity gradient was observed in membrane fractions. The activity gradient persisted when the results were expressed as a function of cellular DNA. These findings indicate that protein kinases display a defined topological segregation along the colonic crypt regions and that during migration to the lumen colonic cells attenuate enzyme signals supposedly related to tissue growth.